Texas John Slaughter : [large type] deadly day in Tombstone - Johnstone, William W.; Johnstone, J. A. (Texas John Slaughter, 2019)
"John Horton Slaughter fought on the blood-soaked battlefields of the Civil War. He drove thundering cattle across a dangerous frontier, and faced the deadliest outlaws as a Texas Ranger. Now, bestselling authors William and J.A. Johnstone tell the story of this towering historical figure-the man who tamed Tombstone, Arizona. A HERO AS BIG AND TOUGH AS TEXAS Enticed by the richest poker tournament the West has ever seen, a horde of cheating and ruthless card players is gathering at Tombstone, Arizona. Lawman John Slaughter already has his hands full when a local Romeo takes off with a rancher's daughter and draws the ire of her father and a blood-thirsty posse. Back in town, a murder shatters the poker tournament, with a beautiful Englishwoman as the prime suspect. John Horton Slaughter has been to hell and back as a soldier, rancher and Texas Ranger, and this just might be his toughest day yet. To set things straight he'll need every bullet he can muster, aim straight, and shoot to kill. And kill again.."--